2008
DOI: 10.5507/bp.2008.007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Multidrug Resistance-Related Protein (Mrp-1), Lung Resistance-Related Protein (Lrp) and Topoisomerase-Ii (Topo-Ii) in Wilms' Tumor: Immunohistochemical Study Using Tma Methodology

Abstract: Aims: MRP-1, LRP and TOPO-II are all associated with protection of the cells from the adverse eff ects of various chemotherapeutics. The aim of this study was to measure the expression of these proteins in Wilms' tumor (WT).Materials and Methods: TMA block was constructed from 14 samples of WT's and from xenografts derived from them. Sections of the TMA were used for immunostaining against MRP-1, LRP and TOPO-IIa.Results: All normal kidneys expressed MRP-1 but were either weakly or negatively stained for LRP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In addition, MDR1 and MRP1 expression levels were detected with western blotting; the results demonstrated that these proteins were also significantly downregulated. These 2 proteins belong to the ABC super-family and are able to pump chemotherapeutic drugs out of the cells (12). Furthermore, the present study also demonstrated that LRP protein expression was downregulated.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, MDR1 and MRP1 expression levels were detected with western blotting; the results demonstrated that these proteins were also significantly downregulated. These 2 proteins belong to the ABC super-family and are able to pump chemotherapeutic drugs out of the cells (12). Furthermore, the present study also demonstrated that LRP protein expression was downregulated.…”
Section: Discussionsupporting
confidence: 56%
“…Lung cancer is the most frequent cancer type worldwide and its incidence increases by 0.5% per year (15). Despite major advances in disease management, chemotherapy and radiotherapy, almost 80% of all patients with lung cancer succumb to the disease within 1 year of diagnosis and long-term survival is achieved in only 5-10% of all cases (15,16). The major obstacle in lung cancer chemotherapy is inherent and acquired drug resistance of the cancer cells (17,18), which limits the efficacy of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…1 In contrast to the significant reduction of mortality from heart disease, the survival rate of lung cancer patients has been at a plateau for almost three decades, with a relative 5-year survival rate of <18% in most countries. Because of the size and distribution of lung cancer, the cytoreductive surgery is not very effective for this disease and therefore chemotherapy and/or radiation are the only treatments of choice.…”
Section: Introductionmentioning
confidence: 99%
“…Despite major advances in patient management, chemotherapy and radiotherapy, nearly 80% of the patients still die within 1 year of diagnosis and long-term survival is obtained only in 5–10% of the cases. 1 …”
Section: Introductionmentioning
confidence: 99%